2020
DOI: 10.24127/jpf.v8i2.2910
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Efektivitas Media Pembelajaran E-Learning Dalam Meningkatkan Hasil Belajar Siswa Sma Pada Pelajaran Fisika

Abstract: Pendidikan merupakan kebutuhan sepanjang hayat. Setiap manusia membutuhkan pendidikan dimanapun ia berada dan sepanjang hidupnya. Dalam proses pembelajaran yang berkualitas terdapat beberapa aspek yang turut mempengaruhi salah satunya penggunaan media pembelajaran yang inovatif. Pada mata pelajaran fisika guru cenderung kurang kreatif dan inovatif dalam menerapkan media pembelajaran saat mengajar,sehingga kurangnya motivasi belajar siswa yang dapat mempengaruhi hasil belajar siswa. Perkembangan teknologi infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 0 publications
1
6
0
8
Order By: Relevance
“…The platform, on average, aids students in increasing their desire to learn and improving their learning outcomes. The current study results align with Affandi et al (2020) and Muharto et al (2017), who researched the effectiveness of e-learning on student learning outcomes. This can be done because students can learn flexibly with no time and place-bound.…”
Section: Findings and Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The platform, on average, aids students in increasing their desire to learn and improving their learning outcomes. The current study results align with Affandi et al (2020) and Muharto et al (2017), who researched the effectiveness of e-learning on student learning outcomes. This can be done because students can learn flexibly with no time and place-bound.…”
Section: Findings and Discussionsupporting
confidence: 91%
“…The results of previous research prove that e-learning can improve students' learning outcomes effectively. Affandi et al (2020) explained that e-learning in physics learners affects student learning outcomes where the lowest effectiveness score is 21.72%, the highest at 94.47%, and the average score is 69.67%. The similarities in the current research are that e-learning contributes effectively to improving the desire to learn and the learning outcomes of students.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…This media provides space for educators (both teachers and lecturers) to closely monitor and facilitate student and student learning progress (Alfina, 2020). The results of research conducted by Affandi (2020) on the Analysis of the Effectiveness of E-Learning Learning Media in Improving the Learning Outcomes of Class X Students in Physics Lessons using the meta-analysis method, namely by combining 8 similar research results found in journals on the Google Scholar site, with the keywords "E-Learning Learning Effectiveness" by finding that each study has different effectiveness values. Based on the results of the analysis, it turns out that the E-learning learning media is effective in improving student learning outcomes with the lowest effectiveness score of 21.72% to the highest 94.47% with an average of 69.67%.…”
Section: Resultsmentioning
confidence: 99%
“…In the development process, advanced skills are needed for teachers so that they can produce an interesting and educative online learning media and can increase students' motivation and interest in learning. Affandi (2020) added that the success of students in online learning, especially the use of online learning media can be influenced by internal and external factors. Internal factors are factors that come from oneself such as talent, health and others.…”
Section: Resultsmentioning
confidence: 99%
“…Bukan hanya itu, pembelajaran yang menggunakan e-learning dapat memfasilitasi adanya keterbatasan ruang dan waktu antara peserta didik dengan guru, peserta didik dengan peserta didik, serta peserta didik dengan materi. Salah satu cara untuk menerapkan e-learning dalam model pembelajaran adalah dengan menggunakan media Edmodo [6]. Edmodo merupakan perangkat lunak yang mampu memfasilitasi peserta didik dalam kegiatan pembelajaran Berdasarkan latar belakang di atas maka permasalahan dalam penelitian ini adalah bagaimana meningkatkan keterampilan pemecahan masalah fisika dan kemampuan komunikasi peserta didik pada materi impuls momentum siswa kelas X MIPA 8 di SMA Negeri 6 Yogyakarta.…”
Section: Pemanfaatan Edmodo Dalam Pembelajaran Fisika Untuk Meningkat...unclassified